1994
DOI: 10.1007/bf02111909
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cynical hostility and PTSD among vietnam veterans

Abstract: The personality construct of cynical hostility, as measured by the Cook-Medley scale (an MMPI subscale)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
3
21
1
1
Order By: Relevance
“…These findings are consistent with the results of Chemtob et al (1994), in which the mean scores and standard deviations on the BDHI and the Anger Expression Scale were similar to the present results. The data are also consistent with the findings of Kubany et al (1994) in that measures of anger and PTSD were significantly correlated with one another, indicating a direct interrelationship between anger and PTSD severity. The data also showed that anger varied as a function of employment status, but not compensation-seeking status.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are consistent with the results of Chemtob et al (1994), in which the mean scores and standard deviations on the BDHI and the Anger Expression Scale were similar to the present results. The data are also consistent with the findings of Kubany et al (1994) in that measures of anger and PTSD were significantly correlated with one another, indicating a direct interrelationship between anger and PTSD severity. The data also showed that anger varied as a function of employment status, but not compensation-seeking status.…”
Section: Discussionsupporting
confidence: 91%
“…One implication of these findings is that, based on the established link between anger and heart disease (e.g., Smith, 1992;Spielberger et al, 1991), veterans with PTSD may be at increased risk for cardiac difficulties. Thus, these data supports previous suggestions (e.g., Kubany et al, 1994) that high levels of anger may lead not only to potential difficulties with interpersonal functioning, but also to physical health problems in veterans with PTSD. Certainly this is a population who have demonstrated dramatic levels of health problems in recent years (e.g., Kulka et al, 1990;Litz, Keane, Fisher, Marx, & Monaco, 1992), and hostility may be one of several factors to account for this.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations